Integrating Urban Sculpture Art and Environmental Space: Enhancing Community Engagement and Physical Activity in Sports-Centric Urban Design - Jingwen Lv, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Urban sculpture art serves as a cultural and visual representation of a city's spirit, ethos, and cultural atmosphere, subtly shaping the psychological and social experiences of its residents. By creating engaging public spaces, urban sculptures not only reflect cultural identity but also inspire active participation and community engagement. In the context of cultural and creative industries, urban sculpture plays a pivotal role as both a driver of innovation and a carrier of urban culture, offering unique opportunities to foster creativity and collaboration in urban environments. This study explores the integration of urban sculpture art with environmental spaces, focusing on its potential to promote physical activity and psychological well-being in sports-centric urban designs. Through an analysis of urban sculptures’ roles in shaping environmental dynamics, this paper highlights how strategic placement and thematic design can enhance outdoor spaces for recreational and sports activities. By bridging the cultural and physical dimensions of urban spaces, this integration aims to foster environments that encourage active lifestyles, community cohesion, and holistic well-being, aligning with the principles of sports psychology and urban development.